Multiplex Screening Assay for Identifying Cytotoxic CD8+ T Cell Epitopes - Poh, Chek Meng; Zheng, Jian; Channappanavar, Rudragouda; Chang, Zi Wei; Nguyen, Thi H. O.; Rénia, Laurent; Kedzierska, Katherine; Perlman, Stanley; Poon, Leo L. M. (Frontiers in Immunology, 2020)
The cytotoxicity of epitope-specific CD8+ T cells is usually measured indirectly through IFNγ production. Existing assays that directly measure this activity are limited mainly to measurements of up to two specificities in a single reaction. Here, we develop a multiplex cytotoxicity assay that allows direct, simultaneous measurement of up to 23 different specificities of CD8+ T cells in a single reaction. This can greatly reduce the amount of starting clinical materials for a systematic screening of CD8+ T cell epiptopes. In addition, this greatly enhanced capacity enables the incorporation of irrelevant epitopes for determining the non-specific killing activity of CD8+ T cells, thereby allowing to measure the actual epitope-specific cytotoxicity activities. This technique is shown to be useful to study both human and mouse CD8+ T cells. Besides, our results from human PBMCs and three independent infectious animal models (MERS, influenza and malaria) further reveal that IFNγ expression by epitope-specific CD8+ T cells does not always correlate with their cell-killing potential, highlighting the need for using cytotoxicity assays in specific contexts (e.g., evaluating vaccine candidates). Overall, our approach opens up new possibilities for comprehensive analyses of CD8+ T cell cytotoxicity in a practical manner.